The Impact of Liquidity, Total Asset Turnover, Company Size, and Sales Growth on Profitability in Automotive Manufacturing Companies from 2019 to 2022 - Rizqullah, Naufal; Mujiyati, Mujiyati (PT Mattawang Mediatama Solution, 2024)
This study is based on the business phenomenon that occurred in the manufacturing companies of the automotive and parts industry from 2019 to 2022. The business phenomenon is the decline in profits of the manufacturing companies of the automotive and parts industry. In addition, there are differences in the results of the studies on the factors that affect profitability. The strategy to solve this problem is to apply factors such as liquidity (CR), total capital turnover (TATO), company size and sales growth and profitability (ROA). The subjects of this study include all the manufacturing companies in the automotive and parts industry during the period of 2019-2022, a total of 16 companies. The sample of this study is 11 manufacturing companies in the automotive and parts industry during the period of 2019 to 2022. The sampling was done by purposive sampling. The data analysis technique used multiple linear regression.